Peran Pelatihan Berbasis Kompetensi dalam Meningkatkan Produktivitas Tenaga Pendidik di Era Digital - Dinda Putri; Khalisatun Husna; Muhammad Arby Fahrezi; Tengku Darmansah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
The development of digital technologies has changed the educational landscape, requiring educators to upgrade their skills to remain relevant and effective. Competency-based training is important in this context because of its focus on developing practical skills that can be directly applied in teaching. This paper discusses the role of competency-based training in improving educators’ productivity in the digital era. The method used is a literature study, which includes analysing various studies and articles related to this topic. The findings show that competency-based training acts as: 1) Skills Development; 2) Teaching Quality Improvement; and 3) Evaluation of Teaching Effectiveness. The purpose of this study is to provide insights into the importance of competency-based training in improving the productivity and teaching quality of educators in the digital era, and to encourage wider and more sustainable implementation of training.